MOTIVATIONAL STRATEGIES IN TEACHING FOREIGN LANGUAGES: MOTIVATIONAL STRATEGIES IN TEACHING FOREIGN LANGUAGES - Nurzhanova, Zhainash; Sagiidolla , Tomiris (Журнал иностранных языков и лингвистики, 2025)
daily lives and during the learning process. Typically, we are discussing circumstances in which the language of education differs from the language of the family or environment. For example, a student can speak Kazakh at home while studying Russian or English at school